Individual repeatability in the timing of river entry indicates the strong influence of photoperiod in the spawning migrations of iteroparous twaite shad Alosa fallax - Yeldham, Mark I.A.; Britton, J. Robert; Crundwell, Charles; Davies, Peter; Dodd, Jamie R.; Nunn, Andrew D.; Velterop, Randolph; Bolland, Jonathan D. (Hydrobiologia, 2023)
The timing of entry into freshwater by mature anadromous fishes is an important component of their migration phenology. In iteroparous anadromous species, identifying the migration cues that influence the timing of entry into freshwater, and annual variability in these timings, is important in assessing the extent of individual repeatability. Here, passive acoustic telemetry tracked 71 twaite shad Alosa fallax (‘shad’) returning to the River Severn’s upper estuary over successive spawning seasons, providing individual information on river entry timing and the associated migration cues. The timing of shad returning to the river (defined as their first detection on an acoustic receiver in the upper estuary) was consistent between years and strongly predicted by photoperiod (as increasing day length), whereas water temperatures and flow rates were weak predictors and highly variable between years. Timings of river entry of individual shad were also consistent across consecutive spawning migrations, indicating high individual repeatability. The application of acoustic telemetry in this study thus revealed high repeatability in the timing of annual spawning migrations, which were cued mainly by increasing day length and that, being seasonally predictable, should ensure entry into freshwater with sufficient time to arrive in spawning areas when in-river environmental conditions are favourable.